Perceived Competence of Ground Staff in Dealing with Unruly Passenger Behavior at Manila International Airport Authority Airports - Oscar Abuan; RHEM RICK CORPUZ; Renel Cruz; Edelito Deles (MultiTech Publisher, 2023)
Abstract: Unruly passenger behavior poses a significant challenge to the airline industry, affecting safety, security, and customer satisfaction. Ground staff play a crucial role in managing these behaviors, and their perceived competence is pivotal in shaping passengers' overall experiences. Passengers' perception of ground staff competence depends on factors such as staff knowledge of airline policies, de-escalation techniques, and their projection of confidence in handling unruly passengers. Airlines have an opportunity to enhance ground staff competence through comprehensive training, clear policies, and a culture of support and teamwork. The study aims to assess and describe the perceived competence of ground staff in dealing with unruly passenger behavior at Manila International Airport Authority airports. A quantitative research design used a survey as the primary data collection method. Stratified and convenience sampling methods were combined to select 1,475 respondents, representing a diverse sample. Data was analyzed using mean scores, standard deviation, and variance to assess the perceived competence of ground staff. The data suggests that ground staff generally exhibit competence in dealing with unruly passenger behavior. However, competence may vary in specific situations, such as when passengers exploit minor anomalies or use their social status for additional services. Overall, ground staff are perceived as competent, particularly in handling passengers displaying potentially violent tendencies. The findings of this study reveal that ground staff at Manila International Airport Authority airports are generally perceived as competent in handling unruly passenger behavior. While competence may vary in specific situations, such as when passengers exploit minor anomalies, overall, ground staff are well-equipped to ensure passenger safety and a smooth travel experience. The study highlights the importance of ongoing investment in staff training and resources to improve the competence of ground staff in addressing unruly passenger behavior, ultimately contributing to passenger satisfaction and safety.